INDEPENDENCE AND TRANSPARENCY OF JUDGES IN ADJUDICATING CASES IN INDONESIA AND THAILAND: A COMPARATIVE ANALYSIS OF JUDICIAL PRACTICE - Yushar, Mhd Faiz; Harisman, Harisman (Universitas Dharmawangsa, 2024)
The independence and transparency of judges are fundamental principles of a fair justice system. However, in some countries, their practice is often affected by various external factors, which can undermine the integrity of the judicial process. This study analyzes a comparison of the practice of independence and transparency of judges in adjudicating cases in Indonesia and Thailand. The purpose of this study is to identify the factors that influence the independence of judges and the level of transparency in decision-making in both countries, as well as evaluate how the legal systems of each country address these issues. The method used was a comparative study with a qualitative approach through document analysis. The results show that although both countries have adopted the principle of judge independence in their constitutions, factors such as political pressure, economic intervention, and local legal culture still affect judge independence and transparency. In Indonesia, although there are adequate mechanisms to guarantee judges' independence, the practice is often hampered by outside influences and a lack of transparency in the judicial selection process. Meanwhile, Thailand faces similar challenges, but with a more open approach to the publication of judicial decisions.